Diabetic nephropathy and quality of life among youths with long‐duration type 1 diabetes: A population‐based cross‐sectional study. Issue 5 (16th April 2019) - Tönnies, Thaddäus; Stahl‐Pehe, Anna; Baechle, Christina; Castillo, Katty; Yossa, Rhuphine; Holl, Reinhard W.; Rosenbauer, Joachim
Abstract : Objective: To investigate whether diabetic nephropathy (DN) is associated with lower quality of life (QOL) in youths with long‐duration type 1 diabetes and whether associations differ by diabetes duration. Methods: Overall, 1, 462 youths aged 11 to 17 years with diabetes onset between 0 and 4 years of age and at least 10 years diabetes duration completed questionnaires on QOL between 2009 and 2016. Chronic generic and diabetes‐specific QOL (diabetes impact and treatment scale) were assessed with three scales of the DISABKIDS instruments. Information on DN was obtained from the diabetes patient follow‐up registry ("Diabetes‐Patienten‐Verlaufsdokumentation") with DN defined as micro‐ or macroalbuminuria. Linear regression analyses were used to evaluate the association between QOL and DN. To adjust for potential confounders, we applied inverse probability of treatment weighting for the linear regression. Results: In adjusted analysis, DN was associated with lower QOL in the chronic generic and the two diabetes‐specific DISABKIDS scales. Overall, the observed effects were not clinically relevant but increased consistently with longer diabetes duration. Among those with at least 16 years diabetes duration, differences in QOL between patients with vs without DN were clinically relevant on the chronic generic scale ( β = −10.3 [−21.0;0.7]). Conclusion: The results suggest that long‐term microvascular complications can impair chronic generic QOL already in youths with type 1 diabetes. Differences in QOL between patients with and without DN seem to increase with diabetes duration.